Continuing education of teachers and the curri-cular document of Roraima: Mathematical kno-wledge in early childhood education - Magalhães, Verônica de Oliveira; Bacchus , Juanita Nadine; Bulcão , Bibiana Araujo Pereira; Sousa , Francisca Angêla de Oliveira (Seven Editora, 2023)
The multiplicity of issues involving teacher training is extensive and this article fo-cuses on some factors related to aspects of continuous training according to the Curri-culum Document of Roraima in the light of BNCC and the inclusion of mathematical knowledge in the five Fields of experiences in early childhood education. It is no-teworthy that there is caution in the approach of mathematics in early childhood educa-tion, because what is aimed at this stage is not to develop only the object of knowledge, but mathematical thinking. The research, qualitative in nature, was conducted with teachers who teach in early childhood education and discuss in the school environment the relevance of continuing education and curriculum. The research aimed to analyze the continuous training as a means of expanding the knowledge and reflection about the teaching work in relation to didactic planning and the integration of mathematical knowledge in the experience fields. Therefore, the question is: "How does the continu-ous training contributes to the implementation of the didactic planning of the early childhood education teacher, making him/her realize that all the experience fields can be permeated by mathematics? For the research, it was used as instrument in the collec-tion of the data a questionnaire applied to 12 teachers participants of a continuing training Workshop and that exercise their functions in the municipal education network of Uiramutã-RR. It is noticed in the results that the conceptual discussions and the planning practices proposed in the continuous training allowed to establish relations between the different mathematical contexts and the experience fields. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-142